Analisis Puisi “Malam Berdarah” Karya Ozy V. Alandika Menggunakan Pendekatan Mimetik - Isyatul Mardhiah (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2025)
Poetry is a beautiful language expressed in written words based on a person's thoughts and feelings. Poetry is a literary work that is imaginative and contains a similarity in meaning with other uses, so the meaning contained in poetry remains hidden behind words, metaphors, and aesthetics and is conveyed. Not everyone can understand the meaning of poetry. In reading poetry, it is necessary to repeat it several times to understand the meaning of the poem because the language in poetry has a broad, implicit meaning and is difficult to interpret. Therefore, readers must understand how to study poetry with knowledge so that they can understand the meaning of the poetry conveyed. The poem "Bloody Night" uses strong and metaphorical language that depicts tragedy and suffering, making it interesting to study. This becomes a reader's attraction to study the poem and make it a research material. The purpose of this research is to analyze the meaning of the poem entitled "Bloody Night" by Ozy V. Alandika and convey the contents of the poem in detail so that readers can know the meaning conveyed through the existence of this research. This research is also beneficial for readers to further develop literary works in the form of poetry. The method used in this research is a qualitative descriptive method that examines the content of the meaning of the poem "Bloody Night". Thus, this research will reveal the implicit meaning of the poem presented by the poet. In addition, the researcher analyzes this poem using a mimetic approach. Mimetic is an approach in literary criticism that considers literary works as imitations or fictions of real life.